2015
DOI: 10.15540/nr.2.3.126
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Discrimination and Control of EEG Alpha

Abstract: The relationship between discrimination and control of physiological states is largely unexplored, although it is often suggested that this relationship is important for the mechanism of action of biofeedback. This pilot study examined 6 participants given seven sessions of alpha discrimination training combined with standard neurofeedback "control" training. Four subjects achieved five criterion (binomial p < .05) sessions in the discrimination task. The discrimination task performances correlated significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…After obtaining informed consent, participants were given a set of instructions describing strategies to relax and reduce muscle artifact, and the phenomenology of alpha and nonalpha states (Frederick, 2012;Frederick et al, 2015). Participants sat in a cushioned chair with eyes closed in a dimly lit, sound-attenuated room.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After obtaining informed consent, participants were given a set of instructions describing strategies to relax and reduce muscle artifact, and the phenomenology of alpha and nonalpha states (Frederick, 2012;Frederick et al, 2015). Participants sat in a cushioned chair with eyes closed in a dimly lit, sound-attenuated room.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found that it was possible to use intertrial time intervals to "cheat" in the standard Kamiya paradigm, although subjects did not make significant use of this information (Frederick, Dunn, & Collura, 2015;Frederick et al, 2016). It is possible that some of the significantly correct performance in the self-prompted discrimination paradigm could be explained by attention to time cues rather than genuine discrimination.…”
Section: Response Timingmentioning
confidence: 97%
See 1 more Smart Citation